Probiotic and Triticale Silage Fermentation Potential of Pediococcus pentosaceus and Lactobacillus brevis and Their Impacts on Pathogenic Bacteria - Ilavenil Soundharrajan; Dahye Kim; Palaniselvam Kuppusamy; Karanan Muthusamy; Hyun Jeong Lee; Ki Choon Choi (Microorganisms, 2019)
The purpose of this study was to identify potent lactic acid bacteria that could have a great impact on triticale silage fermentation at different moisture levels and determine their anti-bacterial activity and high probiotic potential. For this purpose, Pediococcus pentosaceus (TC48) and Lactobacillus brevis (TC50) were isolated from fermented triticale silage. The fermentation ability of these isolates in triticale powder was studied by an ensiling method. TC48 had higher ability to ferment silage powder by increasing the lactic acid content of silage than TC50. Extracellular supernatant (ECS) of TC48 and TC50 exhibited strong antibacterial effects (inhibition zone diameters: 18−28 mm) against tested cattle pathogenic bacteria with minimum inhibitory/ minimum bactericidal concentrations (MIC/MBC) values of 5.0−10 mg/mL and 10−20 mg/mL, respectively. Extracellular supernatant (ECS) of TC48 and TC50 showed antibacterial activities on E. coli, P. aeruoginosa, S. aureus and E. faecalis through destruction of membrane integrity as confirmed by decreased viability, and increased 260 nm absorbing material in culture filtrate of pathogenic bacteria exposed to ECS of both strains. TC48 and TC50 strains exhibited high tolerance to artificial gastric, duodenal and intestinal fluids. TC48 showed good hydrophobicity and auto-aggregations properties. TC48 and TC50 significantly co-aggregated with E. coli, P. aeruoginosa, S. aureus and E. faecalis in a time-dependent manner. In summary, all of the bacteria had a positive impact on at least one functional property of the silage during the fermentation process. However, the addition of P. pentosaceus (TC48) and L. brevis (TC50) yielded the greatest silage quality improvement, having high antibacterial and probiotic properties.